The Characteristic of Anti dsDNA and Organ System Involved in Systemic Lupus Erythematosus Patient at Hasan Sadikin General Hospital, Bandung - Safira Nadifa; Achadiyani Achadiyani; Hartati Purbo Dharmadji; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2017)
Background : Clinical manifestation of Systemic Lupus Erythematosus (SLE) may be varies in attacking various body tissue and organ system. Anti-dsDNA is the important antibody indetermining diagnosis and prognosis of SLE. This study was conducted to explain the characteristics of antidsDNA and organ system involved in SLE patients.Method:Â  We used quantitative descriptive analysis methods. Data were collected from medical records of SLE patients who came to Dr. Hasan Sadikin Bandung General Hospital Rheumatology Clinic from September to November 2016. Using categorical descriptive research equation, we found that total minimum samples were 67 subjects. Data observed included the level of anti-dsDNA antibody and clinical manifestation of organ systeminvolved.Result: From 67 samples, there were 65 females which accounted for 97% of the research subjects. Distribution of organ system involved in our subjects was musculoskeletal (29%), mucocutaneous (27%), hematologic (21%), kidney (15%), neuropsychiatry (4%),lung involvement (4%) and cardiovascular (0%). Organ system involved related with strong positive anti-dsDNA were mucocutaneous (21,6%), hematologic (25%), musculoskeletal (12,5%), kidney (14,3%) and lungs (20%).Conclusion:Â  The most frequent organ system involved in SLE patients at our setting was musculoskeletal. The common organ involvement related with strong positive antidsDNA were mucocutaneous, musculoskeletal, and hematologic. Keywords: anti-dsDNA, involvement of organ system, clinical manifestation, systemic lupus erythematosus